The Status of the Alash Movement and Its Influence on the Formation of National Statehood in the Historiography of Contemporary Kazakhstan - IBRAYEV Akmaral; SAKTAGANOVA, Elmira; MALIKOVA, Saule; TAISHYBAI, Zarkyn; TEMIRKHANOVA, Assemgul; KABDUSHEV, Bolat (Studia Historica Nitriensia)
A well-defined national ideology that can consolidate society is critical for the sustainable development of a country. This paper considers the concept of the Alash movement, which serves as a constituent element of historical memory, playing a pivotal role in the establishment of sovereign Kazakhstani statehood and national self-identification. Several neighboring countries participated in the suppression of large-scale protest actions that took place in Kazakhstan in 2022–2023. These protests indicated the need for a correction of the liberal development model, the re-legitimization of state-political institutions, and the re-identification of the Kazakh nation in interaction with national minorities and neighboring states. This study examines the theoretical and practical legacy of the Alash movement as the initial experience in the creation of independent Kazakhstani statehood. The works of the leaders of the Alash movement form the basis for delineating the physical and mental boundaries of contemporary Kazakhstan within Eurasian, Islamic, and Turkic civilizational spaces. The history of the Alash movement is delineated into the ascending period of 1905–1920 and the descending period of 1921–1937. The research methodology, based on M. Kroh and M. Terry’s study of national movements, facilitates the identification of developmental stages, determination of prerequisites, regularities, and outcomes of the Alash movement within the context of the collapse of the Russian Empire and the formation of the Soviet Union – referred to as M. Terry’s „empire of positive action.“ Content analysis of scholarly and journalistic works reveals the fundamental characteristics of the ideological concept. Event analysis of pre-Soviet and Soviet periods determines the key components shaping the concept of „Alash“ in Kazakhstan’s historical memory. This study defines new directions for understanding the „Alash“ concept. In the conditions of heightened social protests and potential exacerbation of interethnic relations in 2022–2023, the significance of the liberal secular concept of „Alash“ intensifies in the evolution, consolidation, and stabilization of the national consciousness of the contemporary Kazakhstani nation. The sustainable development of the Republic of Kazakhstan is feasible with active participation in Eurasian integration projects and the preservation of internal harmony among ethnicities and faiths. The „Alash“ concept should be integrated into higher and secondary education, shaping sites of historical memory, and informing the work of governmental agencies and the expert community.